Surface morphology and crystallinity of metal oxides in nickel-cobalt binary system - Chang, Sook-Keng; Zulkarnain Zainal,; Tan, Kar-Ban; Nor Azah Yusof, (Universiti Kebangsaan Malaysia, 2012)
The effect of composition on nickel cobaltites prepared by co-precipitation was investigated. Various compositions were synthesised under different heat treatment conditions. The formation mechanism, lattice parameter and crystallite size were determined by various techniques. X-ray dffraction (XRD) analysis revealed that the optimum condition for the formation of single phase nickel-cobalt oxide (NiCo2O4) can be obtained from solution containing Ni: Co ratio of 33.3 mol%: 66.7 mol% with heat treatment at 400 °C. The presence of pure phase NiCo2O4 with the particle size of approximately 34.10 nm was also observed in field emission scanning electron microscopy (FESEM). The crystallinity of the synthesized oxides was improved with the increment of Ni content.